Factors associated with reintegration trajectory following female genital fistula surgery in UgandaAJOG MFM at a Glance - Rachel Bigley, MD, MS; Justus Barageine, MD, PhD; Hadija Nalubwama, MPH; John Neuhaus, PhD; Ashley Mitchell, MPH; Suellen Miller, PhD; Susan Obore, MD; Josaphat Byamugisha, MD, PhD; Abner Korn, MD; Alison M. El Ayadi, ScD (Elsevier, 2023)
BACKGROUND: A female genital fistula, primarily caused by prolonged obstructed labor or after cesarean delivery in resource-limited countries, affects 500,000 to 2,000,000 women worldwide. Fistula is preventable with timely access to high-quality obstetrical care. Access to surgical repair of a female genital fistula has greatly increased over time. However, research surrounding postrepair reintegration, the process of returning to an individual's normal life, remains limited, and further efforts are needed to understand the factors shaping women's ability to rebuild their relationships and lives following repair. OBJECTIVE: This study aimed to characterize the 12-month reintegration trajectory after female genital fistula repair by participant sociodemographic and clinical characteristics. STUDY DESIGN: This study analyzed quantitative survey and medical record data of women (N=60) participating in a longitudinal cohort study assessing recovery after genital fistula repair in Uganda, with baseline and 4 quarterly follow-up assessments in 12 months. The primary outcome of reintegration was assessed using a 19-item postfistula repair reintegration instrument (range, 0-100) where a higher score represents better reintegration. Predictors of interest included parity and living children, quality of life, depressive symptoms at baseline, self-esteem, stigma, trauma, physical symptoms, and social support. We described participant baseline characteristics using means and proportions and estimated a series of mixed-effects linear regression models, including interactions of characteristics with time to understand how these characteristics influence reintegration trajectory in the 12 months after repair. RESULTS: The participants' physical and psychosocial morbidities at baseline were high; more than 80% of participants reported fistula-related physical symptoms, 82% of participants described their general health as poor, and measures of self-esteem, overall social support, and overall quality of life were low. The mean reintegration score at baseline was 33 (standard deviation, 20), which increased to 78 (standard deviation, 19) at 12 months after fistula repair. The participant sociodemographic characteristics statistically associated with reintegration included any living children (β, 1.08; 95% confidence interval, −0.08 to 2.23). Moreover, psychosocial factors significantly affected reintegration with steeper trajectories for women with depressive symptoms (β, 0.89; 95% confidence interval, 0.02-1.75) or women experiencing internalized stigma (β, 0.05; 95% confidence interval, −0.00 to 0.11) and less steep for those with higher self-esteem (β, −0.11; 95% confidence interval, −0.24 to 0.01), overall social support (β, −0.06; 95% confidence interval, −0.12 to −0.01), and partner support (β, −0.21; 95% confidence interval, −0.35 to −0.07). CONCLUSION: Understanding the prominent factors associated with differences in reintegration trajectories across the year after genital fistula surgery has the potential to inform interventions that mitigate challenges and improve women's postrepair recovery experiences.